Anti-Inflammatory Effects of Huangqin Decoction on Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice Through Regulation of the Gut Microbiota and Suppression of the Ras-PI3K-Akt-HIF-1α and NF-κB Pathways - Min-yao Li (Frontiers in Pharmacology, 2020)
ObjectiveHuangqin decoction (HQD), a classical traditional Chinese medicinal formula, has been commonly used to treat gastrointestinal diseases for thousands of years. We investigated the anti-inflammatory effects and underlying mechanisms of HQD on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC).MethodsExperimental mice were given 3% DSS, and HQD (2.275, 4.55, and 9.1 g/kg), or mesalazine (ME, 200 mg/kg) orally for 7 days. Body weight loss, disease activity index (DAI), colon length, histology, and levels of inflammatory cytokines were measured to evaluate the effects of HQD on colitis. The effects of HQD on the Ras-phosphoinositide-3-kinase (PI3K)-Akt-hypoxia inducible factor 1 alpha (HIF-1α) and nuclear factor-kappa B (NF-κB) pathways were evaluated by Western blot analysis. In addition, the gut microbiota was characterized using high-throughput Illumina MiSeq sequencing.ResultsThe results showed that HQD significantly reduced the body weight loss, ameliorated DAI, restored colon length, and improved the intestinal epithelial cell barrier in mice with DSS-induced colitis. The messenger RNA (mRNA) expression levels of inflammatory mediators were decreased following HQD treatment. Furthermore, the Ras-PI3K-Akt-HIF-1α and NF-κB pathways were significantly inhibited by HQD. Finally, treatment with HQD resulted in recovery of gut microbiota diversity.ConclusionsHQD ameliorates DSS-induced colitis through regulation of the gut microbiota, and suppression of Ras-PI3K-Akt-HIF-1α and NF-κB pathways. Our results suggested that HQD may be a potential candidate for treatment of UC.